Effective substitution of ferrous sulfate with iron oxide nanoparticles enhances growth, antioxidant activity, and stevioside accumulation in micro-propagated Stevia rebaudiana - Muhammad, Sher; Khan, Abid Ali; Khan, Muhammad Rameez; Mukhtar, Sidra; Kazmi, Abeer; Ali, Amir; Siddiqa, Ayesha; Aileen Hernández Ramírez, Kayley; Luna-Arias, Juan Pedro; Medina-Pérez, Gabriela; Pelaez-Acero, Armando; Armenta, Silvia; et al. (Frontiers in Plant Science, 2025)
Nanotechnology, particularly the use of iron oxide nanoparticles (IONPs), has gained significant attention in agricultural research due to its potential to enhance plant growth, development, and stress tolerance. However, the green synthesis of IONPs using plant extracts remains underexplored, especially in the context of agricultural applications. In this study, the green synthesis of IONPs using Moringa oleifera leaf extract is reported, with the extract serving as both a reducing and capping agent. The synthesized nanoparticles were characterized using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX), revealing spherical and polygonal shapes with an iron peak at 6.5-7.5 keV, consistent with the expected size and composition. These IONPs were incorporated into Murashige and Skoog (MS) medium to replace the conventional iron source and evaluate their effects on Stevia rebaudiana micropropagation. The results demonstrate that IONPs at lower concentrations (5.60 mg/L) significantly promoted early shoot and root initiation (5.2 and 5.3 days, respectively), while higher concentrations (11.20 mg/L and 22.40 mg/L) delayed growth initiation and inhibited development. Notably, 22.4 mg/L IONPs enhanced leaf growth (length: 3.20 cm, width: 1.90 cm), fresh weight (238.90 mg), and dry weight (20.67 mg), outperforming the positive control (FeSO4·7H2O). IONPs also increased the total phenolic content (TPC) and total flavonoid content (TFC) in plant tissues, with the highest values (4.54 mg GAE/g and 2.07 mg QAE/g) observed at 22.40 mg/L. The antioxidant capacity, measured by DPPH scavenging activity, was significantly enhanced, reaching 89.70%. Additionally, IONPs promoted the accumulation of diterpene glycosides, including stevioside (4.30 mg/g DW) and rebaudioside A (6.70 mg/g DW), especially at higher concentrations. These findings suggest that IONPs, particularly at 22.40 mg/L, are a promising and environmentally friendly alternative to traditional iron sources, offering enhanced plant growth, improved antioxidant defenses, and increased production of valuable secondary metabolites in S. rebaudiana.